PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN KANTIN UIN RIL) - Nurhidayah, Wulan; Nuratia, Zahra; Saputra, Wahyu; Sanjaya, Vicky F (Journal for Management Student (JFMS), 2022)
This research is a test that aims to determine the influence of price and product quality on consumerpurchasing decisions. Number of samples in This research consisted of 90 respondents. Sampling in this research was carried out with a cross-sectional survey design. Data collection is done by sharing form (questionnaire) in the form of an online statement to respondents. Statistical tests were carried out using PLS-based Structural Equation Modeling. Test validity using loading factor values, while the reliability test uses Cronbach'c alpha, com posite values reliability and Average Variance Extracted (AVE). After all the results of the indicator items are used in this research is valid and reliable, then hypothesis testing is carried out. From The three hypothesesproposed were all supported and significant.